Retreatment of Hepatitis C Infection With Direct-Acting Antivirals - Segarra-Newnham, Marisel (Fed Pract, 2020)
BACKGROUND: Treatment of hepatitis C virus (HCV) infection with direct-acting antivirals (DAAs) results in sustained virologic response (SVR) in > 90% of patients. However, some patients required retreatment with newer DAA options. Treatment was selected after consultation with a clinical pharmacy specialist. METHODS: A retrospective chart review of patients at the West Palm Beach Veterans Affairs Medical Center (WPBVAMC) in Florida retreated from January 2015 to December 2019 was conducted. Data collected included HCV genotype, previous therapy, newly prescribed medications, and treatment outcomes. RESULTS: Since 2015, > 900 patients have been treated at WPBVAMC, including 22 patients who had previously failed interferon combined with DAA regimens and 46 patients who needed retreatment after failure with an all-oral therapy. This review documents the outcomes of retreatment with DAA after initial failure to achieve SVR Of 28 patients treated with a boceprevir-based regimen, 10 ended in failure. All 10 were retreated, and all achieved SVR with ledipasvir/sofosbuvir. Of 53 patients treated with a sofosbuvir-based interferon regimen, 12 failed treatment. All 12 were retreated and all achieved SVR. Thirty patients were retreated after failure with an all-oral DAA. Of 27 tested, 21 achieved SVR. All patients who failed therapy again had cirrhosis. CONCLUSIONS: Veterans retreated with DAAs for HCV infection had a high success rate. Repeat failures of DAAs were rare, but cirrhosis seems to be common among these patients.